Climate trends on the extreme winds in Brazil. (August 2017) - Pes, Marcelo P.; Pereira, Enio B.; Marengo, Jose A.; Martins, Fernando R.; Heinemann, Detlev; Schmidt, Michael
Abstract: The main source of electricity in Brazil is from hydro, which has about 65.2% share of the country's electric energy matrix. However, over the last decade the wind energy increased from 19 MW to 2.2 GW. Since wind is an intermittent energy source, heavily determined by the weather and climatic conditions, and important effects on wind power generation can be expected in the mid and long term, in particular related to the impacts of extreme winds. The IPCC AR5 (Intergovernmental Panel on Climate Change) indicates changes in wind speed at the surface in some regions of the world, and increased wind strength in mid-latitude regions. This study scrutinizes future scenarios of extreme winds in Brazil by applying trend analysis techniques on a 50-year historical series of observational wind speed and meteorological parameters at 10 m height in Brazil. Embracing techniques of cluster analysis it was possible to characterize six main regions with macro climatic similarities. To assess the goodness fit distribution, we designate two stations per homogenous region, taking as criteria the stations with better performance in the qualification process to determine the wind distribution pattern in each region applying the Kolmogorov-Smirnov test (KS) and the lowest standard error (SE). After evaluating the frequency distribution of wind speed, the best fit result for the frequency distribution of maximum wind speed is the Gumbel model. The analysis of climatic trends performed by Mann-Kendall test revealed that in minimum wind speed series is not conclusive because it shows disparate results between homogeneous regions. On the other hand, the analysis of climatic trends of maximum wind speed presents 100% positive trends in Group#1, an equal number of stations with not significant trends and positive trends for Group#2, 36.8% more stations with positive trends than negative trends for Group#3 and 20% of stations with more negative trends than stations with positive trends for Group#4. This way, based in these results, is possible assert that there are an increase in the maximum extreme wind in Brazil, mainly in mid-latitudes. Highlights: The study for winds in Brazil presents a positive trend for maximum wind speed. Cluster analysis applied for wind divided the Brazil into six chief groups. Positive trend for maximum wind speed is consistent with IPCC AR5.